Ebelik Öğrencilerinin COVID-19 Enfeksiyonuyla İlgili Koruyucu Davranışları, Risk Algıları ve COVID-19 Aşı Kabulü - Çelebi, Evrim (KTO Karatay Üniversitesi, 2022)
Amaç:Bu araştırma üniversitede eğitim gören ebelik öğrencilerinin COVID-19 enfeksiyonuyla ilgili koruyucu davranışlarını, risk algılarını ve aşı kabul durumlarını belirlemek amacıyla yapılmıştır. Gereç ve Yöntem: Kesitsel türdeki araştırma 329 ebelik öğrencisi ile yürütülmüştür. Veri toplama aracı olarak çevrimiçi anket formu kullanılmıştır. Veriler SPSS paket programında değerlendirilmiş, analizde ki-kare testi kullanılmıştır. Bulgular: Öğrencilerin %95.4’ü insanların bulunduğu ortama girerken maske taktığını, %93.3’ü kapalı alanların kullanımını azalttığını ve %90’ı ellerini daha sık yıkadığını belirtmiştir. Öğrencilerin %46.2’si kendisinin, %79.6’sı ailesinin COVID-19 ile enfekte olmasından endişe duyduğunu ifade etmiştir. Öğrencilerin %45.9’u COVID-19 aşısı olmak istediğini, %42.6’sı aşıyı ailesine ve arkadaşlarına önerebileceğini söylemiştir. COVID-19 enfeksiyonu geçiren öğrencilerin aşı olma isteği anlamlı düzeyde yüksek bulunmuştur (p

Objective: This study was conducted to determine midwifery students’ COVID-19 infection-related protective behaviors, risk perceptions and acceptance of COVID-19 vaccine who were studying at a university. Material and Methods: This cross-sectional study was conducted with 329 midwifery students. An online questionnaire was used as a data collection tool. The data were analyzed in the SPSS package program and the chi-square test was used in the analysis. Results: Of the students, 95.4% stated that they wore masks when entering an environment including other people, 93.3% stayed in enclosed areas less, 90% washed their hands more often, 46.2% were worried about being infected with COVID-19, 79.6% were worried about their family members’ being infected, 45.9% wanted to be vaccinated against COVID-19, and 42.6% said that they would recommend their family members and friends to receive COVID-19 vaccine. The level of willing to receive vaccine was significantly higher among the students who had had COVID-19 infection (p
Midwifery Students' COVID-19 Infection-Related Protective Behaviors, Risk Perceptions and Acceptance of COVID-19 Vaccine
Keywords: Nursing; Hemşirelik